Oral Non Hodgkin’s Lymphoma : Case Report - เสกธีระ, กรองทิพย์; ทรัพยะโตษก, ไกรสร; รังสิยานนท์, สรสัณห์; บุญสะกันต์, ไพศาล (Journal of Preventive Medicine Association of Thailand, 2019)
Non Hodgkin’s lymphoma is common malignancy seen in HIV patient. This case report presents NHL case in Thai patient who came to see the dentist with complaint of “mass in the mouth”. The dentist assumes a main role in detecting early stage this manifestation. This report also reveals a diagnostic approach of NHL subtype using immunohistochemistry and in situ hybridization of EBV. Complete follow up of case is also presented.